Perception Toward Exposure Risk of COVID-19 Among Health Workers in Vietnam: Status and Correlated Factors - Xuan Thi Thanh Le; Quynh Thi Nguyen; Brenda Onyango; Quang Nhat Nguyen; Quan Thi Pham; Nhung Thi Kim Ta; Thao Thanh Nguyen; Huong Thi Le; Linh Gia Vu; Linh Gia Vu; Men Thi Hoang; Men Thi Hoang; et al. (Frontiers Media S.A., 2021)
Background: Hospital staff are at the frontline for the prevention and control of COVID-19. Understanding their perception of exposure risk is, therefore, important during the early phase of this pandemic. In this study, we evaluated the perception regarding risk of exposure to COVID-19 among Vietnamese hospital staff in Vietnam.Method: A cross-sectional online study was carried out to collect demographic data and risk exposure perception during the second week of the national lockdown in April 2020 in Vietnam. Seven hundred and forty two hospital staff were recruited using the snowball sampling to answer 5-point Likert scale questions regarding their risk exposure perception. Exploratory factor analysis (EFA) was used to examine the construct validity of the questionnaire. Pearson coefficient analysis and multivariable regression models were applied to identify factors associated with the perceived COVID-19 exposure risk.Results: Participants perceived a high risk of being infected with SARS-CoV-2 (score = 3.4, SD = 0.8). They also perceived the workplace response to COVID-19 as inadequate (score = 2.0, SD = 0.5). In particular, participants who worked in the emergency or intensive care departments were more likely to perceive an exposure risk, compared to those in infectious disease control departments (Coef. = −0.38, 95%CI: −0.74; −0.02). Participants from central regions perceived a lower risk of exposure to COVID-19 than those from northern regions (OR = 0.52, 95%CI: 0.28-0.96). Nurses were less likely than doctors to report being at risk of exposure to COVID-19 (OR = 0.56, 95%CI: 0.33-0.95).Conclusions: We identified a high level of perceived risk regarding COVID-19 exposure among hospital staff during the unprecedented lockdown period in Vietnam. A comprehensive approach, incorporating improved risk communications, safety training and psychological support programs, for all hospital staff, including nurses and those residing in high population density areas, might further strengthen the national effort to control the pandemic.